In Situ Heating Neutron and X‐Ray Diffraction Analyses for Revealing Structural Evolution during Postprinting Treatments of Additive‐Manufactured 316L Stainless Steel. Issue 4 (17th November 2021) - Kawasaki, Megumi; Han, Jae-Kyung; Liu, Xiaojing; Onuki, Yusuke; Kuzminova, Yulia O.; Evlashin, Stanislav A.; Pesin, Alexander M.; Zhilyaev, Alexander P.; Liss, Klaus-Dieter
Abstract : Herein, lab‐scale X‐ray diffraction and in situ heating neutron diffraction analyses for evaluating the structural changes at postprinting nanostructuring and structural relaxation upon heating, respectively, in an additive‐manufactured (AM) 316L stainless steel are conducted. The nanostructured AM steel after nanostructuring by high‐pressure torsion reached crystallite sizes of 23–26 nm, a dislocation density of ≈45 × 10 14  m −2 and a microstrain of >0.008. A limited amount of deformation‐induced ε ‐martensite was observed at a local region in the nanostructured AM steel. The time‐resolved neutron diffraction experiment upon heating successfully visualizes the sequential structural relaxation and linear thermal lattice expansion in the nanostructured AM steel. In practice, by calculating the changes in crystallite sizes, microstrains, and dislocation densities, the relaxation behaviors of the nanocrystalline AM steel is observed: 1) recovery with slow stress relaxation with increasing hardness up to 873 K, 2) recrystallization with accelerated stress relaxation at 873–973 K; and 3) grain growth above 973 K with (iii′) total stress relaxation in lattices up to 1023 K. In addition, this manuscript makes connections between the critical subjects in materials science of advanced manufacturing, metal processing and properties, and novel time‐resolved characterization techniques. Abstract : Herein, for the first time, structural evolution during nanostructuring by severe plastic deformation and structural relaxation upon heating in an additive‐manufactured 316L stainless steel by applying the characterization techniques of X‐ray diffraction and in situ neutron diffraction analyses are demonstrated. This study bridges the gaps between the interdisciplinary research of advanced manufacturing, materials synthesis and processing, and novel characterization techniques.